THE RELATIONSHIP BETWEEN DEMOGRAPHIC FACTORS AND INDIVIDUAL PERCEPTION ABOUT COVID-19 VACCINES: PERCEPTION ABOUT COVID-19 VACCINES - Tasnim Tasnim (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background: The cases of Covid-19 disease continue to rise in Kendari city, Southeast Sulawesi Province, Indonesia. In 2020, the task force of  Covid-19 cases reported there were about 3,736 people who got Covid-19 diseases in Southeast Sulawesi Province.To reduce the cases, the Indonesian government have prepared some of covid-19 vaccines. However, the majority of community in this Province are still hesitant to accept covid-19 vaccines. Therefore, this study aimed to understand the relationship between demographic factors and individual perception about covid-19 vaccines surrounding people in Southeast Sulawesi Province. Methods: This study was conducted since January 2020 until October 2020 in Southeast Sulawesi Province of Indonesia. This study recruited 210 respondents with 95% of interval confidence. Dependent variables were demographic factors which comprised age, sex, educational status, mariage status and occupation. Independent variable was individual perception about covid-19 vaccines. Data collection used Google form which was sent through WhattsApp of social media. Statistical analysis used chi-square test and Cramer’s test to understand significant association. Results: This study showed Sex had significant association with individual perception about covid-19 vaccines (P value=0.041<0.05; Cramer’s value=0.174). However, age, educational status, mariage status, and occupation were not associated significantly with the individual perception about covid-19 vaccines. Female had better perception than male about covid-19 vaccines. Conclusions: This study shows that female have more information than male about covid-19 vaccines. This is caused by several media to get information including female organizations in the village such as women organization, islamic women organization and social media groups. Women is more communicative than male.